Nilai Karakter Pembelajaran Pendidikan Pancasila dalam Ritual Larung Sesaji Telaga Ngebel di Desa Ngebel - Prastyawan, Oky Dwi; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2025)
Learning is an effort to encourage students to engage in learning activities so that they can gain understanding. Educators can use the culture present in society to teach. The Larung Sesaji Telaga Ngebel ritual is one of the cultures present in the community. This is a hereditary ritual performed once a year as a way for the community to express gratitude for the abundant harvest. Religious values, tolerance, hard work, democracy, love for the homeland, and social concern can be derived from the Larung Sesaji Telaga Ngebel. The purpose of this writing is to understand (1) how the Larung Sesaji Telaga Ngebel ritual is performed and (2) the character values that can be learned from the ritual. The conclusion is that the Larung Sesaji ritual is highly relevant for education and reflects many character values such as tolerance, hard work, democracy, love for the homeland, and social concern.